A new pseudo binary strategy to design eutectic high entropy alloys using mixing enthalpy and valence electron concentration. (5th April 2018) - Jin, Xi; Zhou, Yang; Zhang, Lu; Du, Xingyu; Li, Bangsheng
Highlights: A pseudo binary strategy was proposed to design eutectic high entropy alloys; An eutectic high entropy alloy can be obtained by mixing a stable FCC-structured solid solution and a stable IMC; Three eutectic high entropy alloys were successfully prepared using this strategy; All the three alloys exhibited excellent tensile properties, with fracture strength > 1000 MPa and elongation > 10%. Graphical abstract: Abstract: Eutectic high entropy alloys (EHEAs) have attracted wide attention of material scientists and engineering scientists due to the good castability, phase stability as well as excellent mechanical properties. However, it still remains a huge challenge to design EHEAs accurately on account of the inaccuracy of multicomponent phase diagram calculation and complexity of experimental exploration. Here, a simple and practicable pseudo binary method was proposed to design EHEAs using the parameters of valence electron concentration (VEC) and mixing enthalpy (△Hmix ). Using this strategy, a series of nanostructured EHEAs composed of ordered body centered cubic (B2) phase and face centered cubic (FCC) phase were successfully developed. All the designed alloys in the current work exhibited excellent comprehensive mechanical properties, with a tensile fracture strength higher than 1000 MPa and a total elongation > 10%. The combination of high strength and good plasticity indicates a significant potential application in engineering field. Furthermore, this new strategy is not only suitable for the current work but also available for the majority of reported EHEAs, which shows great universality in designing EHEAs.